A gender based comparison and correlation of spatiotemporal gait parameters and postural stability: Gait Parameters and Postural Stability - Al-Makhalas, Abdulhadi; Abualait, Turki; Ahsan, Mohammad; Abdulaziz, Sahar; Al Muslem, Wafa (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Postural stability during gait is a crucial factor that reduces the risk of falls. Researchers determine the most effective way to assist patients whose postural stability deficit predominantly related to gait parameters. The aim of this study was to investigate the comparison and relationship between spatiotemporal gait parameters and postural stability in young male and female. Methods: 96 participants (male, and female) with age range from 18-40 years were selected to conduct this cross-sectional correlation study. Any participants with cardiovascular, neuromuscular diseases, musculoskeletal injury, vision, and hearing problem were excluded from the study. To measure spatiotemporal data, the Physilog application by Gaitup was used. Stabilometer was used to assess unipedal dynamic postural stability. Statistical analysis of data was performed by using SPSS software. Mann Whitney U test, Kruskall Wallis H test, and Spearman rank correlation coefficient tests were used to statistical analysis. Results: The results of this study revealed that anteroposterior stability for left leg was significant (p=.002) between male and female. The gait parameters as stride length (Left Leg, p=.050), (Right leg, p=.001); gait speed (Left Leg, p=.006), (Right leg, p=.009); and maximal heel clearance (Left Leg, p=.001), (Right leg, p=.001) were significant between genders. No significant relationship was found among the dynamic postural stability and spatiotemporal parameters of gait. Conclusions: In summary, this research illustrates the putative mechanisms of gait parameters and postural dynamic stability parameters differences in male and female participants and also relationship among them